2021
DOI: 10.3892/ijo.2021.5174
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapies for malignant pleural effusion: Anti‑angiogenic therapy and immunotherapy (Review)

Abstract: Patients with a variety of malignancies can develop malignant pleural effusion (MPE). MPE can cause significant symptoms and result in a marked decrease in quality of life and a poor prognosis. MPE is primarily considered as an immune and vascular manifestation of pleural metastases. In the present review, the existing evidence supporting the applicability of anti-angiogenic therapy and immunotherapy for the treatment of MPE was summarized. Patients with MPE have benefited from anti-angiogenic agents, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…Li et al recommended that nanomedicine should be desired to improve not only the safety but also the efficacy of immunotherapy ( Li and Kataoka, 2021 ). For malignant pleural effusion, tumors and inflammation that stimulate pleural thickening and fibrosis, PD-1 inhibitors are difficult to enter the pleural cavity from peripheral blood and accumulate in sufficient drug concentrations ( He D. et al, 2021 ). Our results showed that intrapleural administration of PD-1 inhibitors rapidly activated T cells and had a high anti-tumor effect in the short term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al recommended that nanomedicine should be desired to improve not only the safety but also the efficacy of immunotherapy ( Li and Kataoka, 2021 ). For malignant pleural effusion, tumors and inflammation that stimulate pleural thickening and fibrosis, PD-1 inhibitors are difficult to enter the pleural cavity from peripheral blood and accumulate in sufficient drug concentrations ( He D. et al, 2021 ). Our results showed that intrapleural administration of PD-1 inhibitors rapidly activated T cells and had a high anti-tumor effect in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of lymphocytes enter the pleural cavity during the formation of pleural effusion; however, their anti-tumor immune activity is significantly reduced. Activating these lymphocytes in vitro can significantly enhance their tumor killing ability and effectively alleviate the occurrence of malignant pleural effusion ( He D. et al, 2021 ). Tumors and inflammation can stimulate pleural thickening and fibrosis, and systemic drugs are difficult to accumulate in the pleural cavity at concentrations that can effectively kill cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of oxygen, HIF-1α can make VEGFmRNA more stable, increase the transcription level of VEGF receptors, and produce a large number of new blood vessels [9]. The action of VEGF is primarily mediated by endothelial cell receptors VEGFR-1 and VEGFR-2 [10]. VEGF binds to its receptors and induces downstream signaling such as PKC and MAPK, a process that induces vascular endothelial cell differentiation and proliferation, thereby promoting cancer growth and MPE production [11].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, human endostatin was engineered and modified with a nine-amino acid sequence at the Nterminal to improve solubility and stability and is currently available under the brand name Endostar. 3,66 In 2014, Zhao et al conducted an RCT evaluating the clinical efficacy and safety of intrapleural Endostar when added to cisplatin/pemetrexed chemotherapy compared with standard regimen of cisplatin/pemetrexed for patients with MPE due to nonsquamous NSCLC. 67 The treatment outcomes were defined according to the World Health Organization guidelines: CR, PR, NC, and progressive disease.…”
Section: Antiangiogenic Therapymentioning
confidence: 99%